Jemuran Otomatis Menggunakan Sensor LDR, Sensor Hujan Dan Sensor Kelembaban Berbasis Arduino Uno - yayan hendrian; Yusuf Pribadi Yudatama; Violetta Surya Pratama (JURNAL TEKNIK KOMPUTER, 2020)
The condition of weather changes in Indonesia is uncertain, so it difficult to predict clear and rainy weather. This is still a major problem for people who are drying clothes especially in the rainy weather conditions. Usually clothes is often left out traveling, with weather conditions like this make some people feel anxious because they do not have time to lift the clothesline in the rainy weather conditions. To overcome these problems the authors make an automatic clothesline prototype using LDR sensor, rain sensor, and moisture sensor using Arduino Uno. In addition to these sensors there are also additional such as fans and DC motors. From the results of testing tools that have been made tools can work well. The tool can work when the sensor will read the weather around, LDR sensor and rain sensor function to detect the weather around, while the humidity sensor serves to detect the condition of the clothes whether in wet or dry conditions.